Penguatan Program Vaksinasi Covid-19 Di Wilayah Puskesmas Made Surabaya Barat - Ritunga, Imelda; Lestari, Sarah Hagia; Santoso, Jemima Lewi; Effendy, Laij Victor; Siahaan, Salmon Charles Pardomuan Tua; Lindarto, Wira Wijaya; Nurhadi, Stefany; Irham, I Made Muhammad; Monica, Tasya (Universitas Nusantara PGRI Kediri, 2021)
Vaccination aims to have a specific impact on a certain disease so that one day you will be exposed to the disease, you will not get sick or only experience mild illness. Indonesia is carrying out the COVID-19 vaccination as part of the COVID-19 pandemic prevention strategy, with the implementation of the COVID-19 vaccination aimed at protecting the public from SARS-CoV-2 infection which can cause illness and death due to COVID-19. The vaccination program is carried out by the government in 4 stages carried out by the Puskesmas as an extension of the local Health Office. Puskesmas are the spearhead of the implementation of the vaccination program for the community. Puskesmas Made Surabaya oversees several higher education institutions in the region. In carrying out the implementation of the phase 2 vaccination with a larger coverage, it requires the assistance of health workers and a place of implementation that facilitates access to services. Vaccination activity phase two is a government program and Puskesmas Made requires the support of health personnel and a place of service that facilitates access to vaccination services. Solutions in the form of assistance for health workers and a place for vaccine implementation that facilitate access to implementation are important in the success of the COVID-19 Vaccination program. The methods used are preparation of vaccine officer registration, participating in vaccine officer training and obtaining vaccinator certificates, technical coordination of vaccine implementation at Puskesmas, implementation, and evaluation of vaccination implementation. The results of the activities to achieve vaccination at the Ciputra University Vaccine post for institutions in the working area of ​​the Puskesmas are well made.